2008
DOI: 10.1103/physrevlett.100.257004
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Multiband Many-Body Interactions inLuNi2B2C

Abstract: We present a comprehensive de Haas-van Alphen study on the nonmagnetic borocarbide superconductor LuNi2B2C. The analysis of the angular-dependent effective masses for different bands in combination with full-potential density functional calculations allowed us to determine the mass-enhancement factors, lambda, for the different electronic bands and their wave-vector dependences. Our data clearly show the anisotropic multiband character of the superconductivity in LuNi2B2C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…This calculation gives different BCS-extrapolation data for T c of the larger and smaller OPs, which points to the multiband nature of superconductivity in ErNi 2 B 2 C. Its physical sense is that there are FS parts with a weaker electron-phonon interaction (EPI) in which the temperature induced suppression of superconductivity is faster. This is supported by the calculation of the anisotropy of the EPI parameter in LuNi 2 B 2 C [4], which can vary from 0.3÷0.8 on a spheroidal FS to 1.0÷2.7 on a cube-like FS.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This calculation gives different BCS-extrapolation data for T c of the larger and smaller OPs, which points to the multiband nature of superconductivity in ErNi 2 B 2 C. Its physical sense is that there are FS parts with a weaker electron-phonon interaction (EPI) in which the temperature induced suppression of superconductivity is faster. This is supported by the calculation of the anisotropy of the EPI parameter in LuNi 2 B 2 C [4], which can vary from 0.3÷0.8 on a spheroidal FS to 1.0÷2.7 on a cube-like FS.…”
Section: Discussionmentioning
confidence: 69%
“…As in [19], the pair-breaking parameter γ increases in the vicinity of magnetic transitions, which is natural to attribute to the effect of spin fluctuations under a change of the magnetic order. 4. It has been shown that the proper choice of the scaling factor S in the one-gap GBTK calculation gives the ratio 2∆(0)/kT c ∼3.52 for the gap in the PM region and its BCS-like temperature dependence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unusual properties in the superconducting state led to controversial debates on its nature. In particular, these materials were among the first for which multiband superconductivity was detected [26][27][28][29]. Furthermore, pronounced gap anisotropies have been suggested [30,31].…”
Section: And References Therein)mentioning
confidence: 99%
“…This compound crystallizes in CeScSi or UGeTe prototype structure belonging to the tetragonal I4/mmm space group with lattice parameters a = 3.754 Å and c = 14.488 Å. This prototype structure it is similar to the quaternary LuNi 2 B 2 C which is the prototype structure of many boron-carbide superconducting materials which offer interesting opportunities for the study of multiband behavior and the coexistence between superconductivity and magnetism [8][9][10][11][12][13][14]. Indeed, superconductivity in layer compounds often produces unusual results and at the same time offers a modern view for the occurrence of superconductivity [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%